Physiologic studies on "choking" in judo - Studies on "choking" with reference to the hypophysio-adrenocortical system - Ogawa, S.; Akutsu, K.; Sugimoto, R.; Saiki, H.; Ikawa, Y.; Tsuboi, M. (Association for the Scientific Studies on Judo, Kodokan, 1963)
The present paper is one of a series of studies conducted by the Society for Scientific Research of Judo, Kodokan, on the effect of the technique of " choking" on the human body. " Choking" occupies a special position among the various Judo techniques, and it consists in strangling the neck of the opponent, causing difficulty in breathing and subsequent unconsciousness. A physiologic study of the effect of "choking" on the human body is of special importance to the development of Judo as a sport, and also in the prevention of untoward accidents. Aside from the report by Saito on his electroencephalographic studies, presentations dealing with the physiology of " choking" are almost nil. The present paper deals with a physiologic study of "choking" and the subsequent state of unconsciousness from the point of view of the adaptation reaction of the hypophysio-adrenocortical system. The reaction of the hypophysio-adrenocortical system was investigated by observing changes in the amount of 17-keto-steroid exereted in the urine, and changes in the number of circulating eosinophiles. Furthermore, since difficulty in breathing is observed in the short interval between inception of "choking" and the subsequent state of unconsciousness, it is expected that hypoxia of the central nervous system results. With this in mind, oxygen saturation of the blood taken from the helix of the ear, and blood pressure were measured at different intervals in order to investigate changes in body reaction.